Exposure to extracellular vesicles from Pseudomonas aeruginosa result in loss of DNA methylation at enhancer and DNase hypersensitive site regions in lung macrophages. Issue 11 (2nd November 2021) - Kyung Lee, Min; Armstrong, David A.; Hazlett, Haley F.; Dessaint, John A.; Mellinger, Diane L.; Aridgides, Daniel. S.; Christensen, Brock C.; Ashare, Alix
ABSTRACT: Various pathogens use differing strategies to evade host immune response including modulating the host's epigenome. Here, we investigate if EVs secreted from P. aeruginosa alter DNA methylation in human lung macrophages, thereby potentially contributing to a dysfunctional innate immune response. Using a genome-wide DNA methylation approach, we demonstrate that P. aeruginosa EVs alter certain host cell DNA methylation patterns. We identified 1, 185 differentially methylated CpGs (FDR < 0.05), which were significantly enriched for distal DNA regulatory elements including enhancer regions and DNase hypersensitive sites. Notably, all but one of the 1, 185 differentially methylated CpGs were hypomethylated in association with EV exposure. Significantly hypomethylated CpGs tracked to genes including AXL, CFB and CCL23 . Gene expression analysis identified 310 genes exhibiting significantly altered expression 48 hours post P. aeruginosa EV treatment, with 75 different genes upregulated and 235 genes downregulated. Some CpGs associated with cytokines such as CSF3 displayed strong negative correlations between DNA methylation and gene expression. Our infection model illustrates how secreted products (EVs) from bacteria can alter DNA methylation of the host epigenome. Changes in DNA methylation in distal DNA regulatory regions in turn can modulate cellular gene expression and potential downstream cellular processes.